Influence of europium doping on the crystallization, morphology, and cathodoluminescent properties of PbNb2O6:Eu3+ phosphors - EKMEKÇİ, METE KAAN (My University, 2022)
© 2022, Turkish Chemical Society. All rights reserved.Undoped PbNb2O6 and Eu3+ ion doped PbNb2O6 samples were synthesized by high temperature mixed oxide method, applying a heat treatment temperature of 1250°C and an annealing time of 6 hours. In order to elucidate the structural and optical behavior of PbNb2O6:Eu3+ phosphors, XRD (X-ray diffraction), SEM (scanning electron microscopy), EDS (energy dispersive spectroscopy), CL (cathodoluminescence) and absoption analyses were performed. The X-ray diffraction results showed that the undoped PbNb2O6 sample crystallized in a rhombohedral symmetry while Eu3+ doped samples formed in orthorhombic symmetry. The morphologies of the rhombohedral and orthorhombic grains were examined by SEM-EDS. The CL spectra showed spectral profiles between 580 and 780 nm in relation to the 4f–4f transitions of Eu3+. A strong emission was observed at about 620 nm, corresponding to the red color and associated with the5D0 →7F2 transition of Eu3+, while the undoped sample did not exhibit CL emission of the host which is probably due to the presence of lead in the host structure. In addition, the CL analysis results showed that the emission intensity increased with the increase of Eu3+ ion concentration. The increase in magnetic dipole transition caused by the electron beam radiation effect of the CL with increasing doping concentration is associated with the change of dipole moments of the Eu3+ doped tungsten bronze host and thus differentiating the emission spectrum. UV lamp excited photograph of undoped sample showed blue-violet color while Eu3+ doped phosphors with red color became more significant with increasing Eu3+ concentration.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; cathodoluminescence; Eu3+ doping; PbNb2O6; XRD–SEM; PbNb2O6; XRD–SEM; Eu3+ doping; cathodoluminescence